Genetic association between celiac disease and chronic kidney disease: a two-sample Mendelian randomization study - Zhimin Chen; Zigui Zheng; Bingjing Jiang; Yanfang Xu (Renal Failure)
Objective A two-sample Mendelian randomization (MR) analysis was performed to elucidate the causal impact of celiac disease on the risk of chronic kidney disease (CKD).Methods The study comprised data from three genome-wide association studies involving individuals of European ancestry. The study groups included participants with celiac disease (n = 24,269), CKD (n = 117,165), and estimated glomerular filtration rate levels based on serum creatinine (eGFRcrea, n = 133,413). We employed four widely recognized causal inference algorithms: MR-Egger, inverse variance weighted (IVW), weighted median, and weighted mode. To address potential issues related to pleiotropy and overall effects, MR-Egger regression and the MR-PRESSO global test were performed. Heterogeneity was assessed using Cochran’s Q test.Results We identified 14 genetic variants with genome-wide significance. The MR analysis provided consistent evidence across the various methodologies, supporting a causal relationship between celiac disease and an elevated risk of CKD (odds ratio (OR)IVW = 1.027, p = 0.025; ORweighted median = 1.028, P = 0.049; ORweighted mode = 1.030, p = 0.044). Furthermore, we observed a causal link between celiac disease and a decreased eGFRcrea (ORIVW = 0.997, P = 2.94E-06; ORweighted median = 0.996, P = 1.68E-05; ORweighted mode = 0.996, P = 3.11E-04; ORMR Egger = 0.996, P = 5.00E-03). We found no significant evidence of horizontal pleiotropy, heterogeneity, or bias based on MR-Egger regression, MR-PRESSO, and Cochran’s Q test.Conclusion The results of this study indicate a causal relationship between celiac disease and an increased risk of CKD.